1996
DOI: 10.1080/15216549600201503
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cycloheximide on the expression of LPS‐inducible iNOS, IFN‐β, and IRF‐1 genes in J774 macrophages

Abstract: The effect of cycloheximide (CHX) on the gene expression for inducible NO synthase (iNOS), interferon (IFN)-~ and IFN regulatory factor (IRF)-I was examined in LPSstimulated J774 macrophages. LPS caused increased expression of mRNAs specific for iNOS, IFN-I~, and IRF-1 with different kinetics. Addition of CHX resulted in inhibition of the LPSinduced iNOS gene expression and parallel decrease in NO production. In contrast, expression of IFN-I~ and IRF-1 genes in response to LPS was potentiated in the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…The J774 cell line has been used as an in vitro model to study macrophage activation by LPS (Fujihara et al ., 1994; Briend et al ., 1995; Hattori et al ., 1996). Treatment with LPS promotes differentiation and activation, manifested by up‐regulated expression of specific cell surface antigens, production of reactive nitrogen intermediates, chemokines and cytokines including TNFα and IL‐1β.…”
Section: Resultsmentioning
confidence: 99%
“…The J774 cell line has been used as an in vitro model to study macrophage activation by LPS (Fujihara et al ., 1994; Briend et al ., 1995; Hattori et al ., 1996). Treatment with LPS promotes differentiation and activation, manifested by up‐regulated expression of specific cell surface antigens, production of reactive nitrogen intermediates, chemokines and cytokines including TNFα and IL‐1β.…”
Section: Resultsmentioning
confidence: 99%
“…However, higher concentrations of NO have been shown to decrease embryo development, possibly through the production of free radicals (43). Nitric oxide has also been shown to up-regulate the receptors for growth factors such as epidermal growth factor and those for anchoring proteins and integrins (44,45). The authors suggested that NO may induce the embryo to develop these growth-regulating and -anchoring proteins on the cell surface.…”
Section: Discussionmentioning
confidence: 96%
“…It is already known that IRF1 has a significant role in antibacterial and antiviral responses, induction of apoptosis and tumorigenesis, with several of these processes known to be mediated by iNOS and NO [ 58 ]. Thus, from our results, it is tempting to conclude that IRF1 regulates these processes also through the induction of Irg1 and itaconic acid production.…”
Section: Discussionmentioning
confidence: 99%